ANALISIS KEBUTUHAN PENGEMBANGAN MODUL AJAR BAGIAN TUMBUHAN DAN FUNGSINYA BERBASIS AUGMENTED REALITY BAGI SISWA SD - Lisa Andriani; Harianingsih; Bambang Subali; Sudarmin; Sri Wardani; Eka Titi Andaryani; Wahyu Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The rapid pace of science and technology requires teachers to develop teaching modules that are appropriate, interesting and up-to-date. Students' competence in understanding, reflecting and evaluating informational (non-fiction) texts is low in school education reports. Observation results from the 2023 Computer-Based National Assessment (ANBK) in the 2024 education report card decreased literacy skills from the good category to the medium category. Decreased value from 72 (in 2023) to 68.97 (in 2024). Scientific literacy is needed to know, convey and use the power of science to find solutions to problems. The aim of this research is to develop a teaching module based on Augmented Reality media to increase elementary school students' motivation and scientific literacy. This research is a descriptive study with a qualitative approach carried out at SD Negeri Kaligangsa 3 Tegal City with 20 class IV students. The methods used are interviews, classroom observations, questionnaires, and diagnostic tests of student understanding. Augmented Reality can depict abstract concepts into reality. Augmented Reality is an effective medium for exploring elementary school students' motivation and understanding of scientific literacy as well as increasing literacy competency in educational report cards.